DISTRIBUSI DAN DAERAH JELAJAH LUTUNG (Trachypithecus auratus sondaicus) DI TAMAN WISATA ALAM PANGANDARAN - Teguh Husodo; Erri Noviar Megantara (BIOTIKA Jurnal Ilmiah Biologi, 2002)
ABSTRACTThe study distribution and population of lutung(Trachypithecus auratus sondaicus) in Pangandaran NaturalRecreational Park (TWAP) was conducted in January 2001through census method.  Broad inventory observation wasapplied to identified plant community and dominant plantspecies. There are 12 lutung groups and evenly distributed  in 37,7 ha area of TWAP,  thus the  density  of  lutung  is rangebetween 35-36 groups/km2. Population average on groups as13,1-13,5, 20-21 are maximized and  5-6 are minimizingpopulation.  Composition  of  sex  ratio  average  on  eachgroup  was  1,9 adult  male/group,  6,9-7,5 adult female/group,  2 subadult/group,   2,7-3,2 young/group and1 infant/group. Lutung habitat on TWAP were secondaryforest, with dominance vegetation are laban (Vitexpubescens), kisegel (Dillenia exelsa) and marong(Cratoxylum formosum), nyamplung (Callophylluminophylum), ketapang (Terminalia catappa), waru (Hibiiscustiliaceus) and butun (Barringtonia asiatica). Recorded 40 of 60species have 1 % frequency index were lutung food.  Duringthe studies  members  splitter  recorded  from  their  group, like A, B and C groups  to  A1-1, A1-2, B1, B2, C2-1 and C2-2.  Average  of  territory area  of all groups were 2,78 ha, 6,67ha are maximized and 2,78 ha are minimized.Keyword :Lutung, distribution, homerange, population, PananjungPangandaran Nature Reserve.